2020
DOI: 10.3847/1538-4357/aba04b
|View full text |Cite
|
Sign up to set email alerts
|

Gaia and Hubble Unveil the Kinematics of Stellar Populations in the Type II Globular Clusters ω Centauri and M22

Abstract: The origin of multiple stellar populations in globular clusters (GCs) is one of the greatest mysteries of modern stellar astrophysics. N-body simulations suggest that the present-day dynamics of GC stars can constrain the events that occurred at high redshift and led to the formation of multiple populations. Here, we combine multiband photometry from the Hubble Space Telescope (HST) and ground-based facilities with HST and Gaia Data Release 2 proper motions to investigate the spatial distributions and the moti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 72 publications
3
5
0
Order By: Relevance
“…Stars with different iron abundances of both ω Centauri and M22 share similar ellipticities, while N-rich stars are more flattened than N-poor stars. This fact is consistent with a scenario where distinct processes are responsible for the enrichment in iron and in p-capture elements s [204].…”
Section: Spatial Distribution Of Multiple Populationssupporting
confidence: 90%
See 1 more Smart Citation
“…Stars with different iron abundances of both ω Centauri and M22 share similar ellipticities, while N-rich stars are more flattened than N-poor stars. This fact is consistent with a scenario where distinct processes are responsible for the enrichment in iron and in p-capture elements s [204].…”
Section: Spatial Distribution Of Multiple Populationssupporting
confidence: 90%
“…• Work based on N-body simulations of GC stars has shown that the frequency of binaries among multiple populations and their 3D kinematics and spatial distributions would provide information on the initial configuration of 1P and 2P stars [198,205,275,276]. Nevertheless, observational constraints are provided for a handful of GCs only [201,204,[209][210][211][212]277]. Moreover, these studies are often limited to the central cluster regions, where the initial configuration of 1P and 2P stars have been erased by the GC dynamical evolution.…”
mentioning
confidence: 99%
“…2). Moreover, we found that FG and SG stars are rotating in phase, a feature often found in present-day GCs (Milone et al 2018;Cordoni et al 2020b).…”
Section: Evolution Of the Stellar Componentsupporting
confidence: 65%
“…We now know that 1G and 2G stars share similar kinematic features in dynamically old GCs, or at least in the centermost regions of GCs where the two-body relaxation time is short, because two-body processes have already erased any kinematic differences between mPOPs (Anderson & van der Marel 2010;Libralato et al 2018aLibralato et al , 2019. The outermost regions of GCs are instead less relaxed, and some fingerprints of the initial kinematic differences between mPOPs can still be detected (Richer et al 2013;Bellini et al 2015;Bellini et al 2018;Dalessandro et al 2018aDalessandro et al , 2018bMilone et al 2018;Dalessandro et al 2019;Cordoni et al 2020aCordoni et al , 2020b.…”
Section: Internal Kinematics Of Mpopsmentioning
confidence: 99%